2019
DOI: 10.29333/iji.2019.12232a
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Inquiry-based Learning to Train the Students' Metacognitive Skills Based on Gender Differences

Abstract: In science learning like biology, metacognitive skill needs to be developed. Inquiry-based learning is a learning which may train students' metacognitive skill. This research aimed to: (1) determining the effectiveness of inquiry-based learning in training students' metacognitive skill, and (2) examining the influence of gender difference on the students' metacognitive skills after given the inquiry-based learning. This research used a 4-D research and development model, and one group pre-test and post-test de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 33 publications
4
50
0
5
Order By: Relevance
“…Previous studies on gender differences in self-regulation and metacognition have been generally inconsistent. Jenkins (2018) has reported that male students use more superficial learning tactics as compared to female students, whereas Nunaki et al. (2019) have indicated that female students utilize self-monitoring goal setting and planning as compared to male students.…”
Section: Theorymentioning
confidence: 99%
“…Previous studies on gender differences in self-regulation and metacognition have been generally inconsistent. Jenkins (2018) has reported that male students use more superficial learning tactics as compared to female students, whereas Nunaki et al. (2019) have indicated that female students utilize self-monitoring goal setting and planning as compared to male students.…”
Section: Theorymentioning
confidence: 99%
“…This result compromises with the study of Jagals and Van der Walt (2018) which tells us that students who can manage to imagine abstract concepts in their minds have higher metacognition levels. Nunaki, Damopolii, Kandowangko & Nusantari (2019) revealed that students who are taught with inquiry-based learning method were attracted and highly motivated. They concluded that inquiry-based learning method affected metacognition levels positively.…”
Section: Discussionmentioning
confidence: 99%
“…al. , 2019), Likewise, the use of an inquiry guide-based practicum guide can also help improve students' thinking skills (Nunaki, Damopolii, Kandowangko, & Nusantari, 2019;Nurussaniah & Nurhayati, 2016;Rahmat & Chanunan, 2018).…”
Section: Article Historymentioning
confidence: 99%
“…Currently a variety of information sources are very numerous and easy to obtain. It is becoming a major challenge for educators to prepare students to learn and survive in an era where information flow runs very fast and dynamic (Nunaki, Damopolii, Kandowangko, & Nusantari, 2019). Students are expected to have the provision of useful skills to be able to survive in the digital age.…”
Section: Introductionmentioning
confidence: 99%